Nutrient Composition and Consumer Acceptability of Instant Cowpea Leaf Based Soup - Alpha Boniface Ssonko (Uganda Christian University, 2025)
Cowpea leaves are a nutritious vegetable important in African diets, particularly in Uganda. The research indicated that their utilization is limited by post-harvest losses and nutrient loss during traditional preparation. This study aimed to enhance the sensory and nutritional attributes of an instant cowpea leaf-based soup. The research investigated the impact of incorporating additives such as monosodium glutamate, mono- and di-glycerides of fatty acids, and whey protein on the soup's physicochemical properties and consumer acceptability. The research employed the use of cowpea leaf and orange-fleshed sweet potato flour as starch-based sources, and the soup was processed using extrusion cooking. Proximate and mineral composition were analyzed according AOAC methods, and sensory evaluation determined consumer preferences. This research sought to improve the nutritional value and consumer appeal of cowpea leaf soup, to promote its consumption and address micronutrient deficiencies.